Hereditary and Congenital Causes of Infertility in Buffalo (Bubalus Bubalis) Bulls - Perumal, P.; Srivastava, N.; Srivastava, S. K.; Chamuah, J. K.; Veeraselvam, M. (International Journal of Bio-resource and Stress Management, 2023)
The artificial insemination (AI) technique plays an important role in improvement of conception rate, prevention of sexually transmitted diseases and carryout of genetic material to next generation. The breeding soundness evaluation (BSE) plays an important step in selection of male buffalo for the said above purpose. This evaluation is an effective way, inexpensive and easy method for selection of breeding buffalo bull. In buffalo breeding management programme, the seasonal variation, nutrition, congenital defect, hormonal changes and hereditary plays a critical role in determining the reproductive efficiency in buffalo bull. The information regarding the reproductive efficiency of buffalo bull is meager for breeding soundness evaluation. The genetic defect has spread to next generation from the genetic defective sire and it will cause congenital defect in offspring. To avoid this problem, cytogenetic selection is very useful. So, a male buffalo calf being purchased for breeding purpose must be evaluated for breeding soundness examination. The breeding soundness evaluator should take care of genetic and congenital condition of male animal used for breeding programme.